PERANAN BUMDES AMANAH DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DESA CIBALONG - Annisa Wildani; Deden Sumpena; Acep Aripudin (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This paper aims to determine the BUMDes Amanah program planning, describe the empowerment products that are expected by the community, analyze the outputs of the BUMDes Amanah empowerment towards the economic empowerment of the people of Cibalong Village. The method used in this research is descriptive method with a qualitative approach. Primary data obtained are the results of research in the field, while secondary data obtained from books, documents and journals. Data collection techniques are carried out through observation and interviews with relevant parties. The results showed that the BUMDes Amanah had a role in creating empowered, independent, and prosperous village communities. Villagers feel relief about the price of basic commodities, get venture capital, get entrepreneurial training, and get good services. With the provision of venture capital, then the income of rural communities increased by an average of 40% to 50%, namely from IDR 500,000 / month to IDR 1,000,000 / month. Referring to the dat,it can be concluded that the community economy through the BUMDes program is increasing.